Analisis Penerapan Artificial Intelligence (AI) dalam Meningkatkan Efisiensi dan Akurasi Laporan Keuangan di Era Digital - Yuniar Fitri Andani; Muh. Sajjaj Sudirman (Mappideceng:Jurnal Ekonomi Syariah, 2026)
This research is motivated by the organization's need for a faster, more accurate, and secure financial system amidst rapid technological advancements. The purpose of this research is to understand the role and practices of Artificial Intelligence (AI) application in financial statement preparation, and to examine the impacts and challenges faced in its implementation. The method used is a Systematic Literature Review (SLR) with a descriptive qualitative approach to various literature from 2020-2024 discussing the integration of AI in the field of accounting. The research findings indicate that the implementation of AI can improve work efficiency by automating routine tasks such as transaction recording and financial statement preparation, enhance data accuracy, and provide predictive analytics to support data-driven decision-making. AI also plays a role in detecting errors and potential fraud early on, while simultaneously strengthening the security of financial data. The main challenges that have emerged include the need to improve human resource competencies, cybersecurity risks, and the potential for accountants' roles to diminish due to automation. The synergy between humans and technology is key to creating efficient, transparent, and sustainable modern accounting systems in the digital age.